The shadow on the quilt [large type] : the Quilt Chronicles - Whitson, Stephanie Grace (Whitson, Stephanie Grace. Quilt chronicles, 2012)
Will Juliana Sutton let the shadow of her dead husband's name overpower her feelings for Cass Gregory, who feels unworthy to offer comfort to a woman of Juliana's standing, or will wounded Juliana choose a love she never thought possible?